'Energy expenditure genes' or 'energy absorption genes': a new target for the treatment of obesity and Type II diabetes. (December 2010) - Braud, Sandrine; Ciufolini, Marco; Harosh, Itzik
Several hundred genes associated or linked to obesity have been described in the scientific literature. Whereas many of these genes are potential targets for the treatment of obesity and associated conditions, none of them have permitted the developement of an efficient drug therapy. As proposed by the 'thrifty genotype' theory, obesity genes may have conferred an evolutionary advantage in times of food shortage through efficient energy exploitation, while 'lean' or 'energy expenditure' genes may have become very rare during the same periods. It is therefore a challenge to identify 'energy expenditure genes' or 'energy absorption genes, ' whose mutations or single nucleotide polymorphisms do result in reduced energy intake. We submit that such 'energy absorption' or 'energy expenditure' genes (crucial genes) are potential new targets for the treatment of obesity. These genes can be identified in rare genetic diseases that produce a lean, failure-to-thrive, energy malabsorption or starvation phenotype.